Etika di dalam Pesan Yesaya - Aaron Heng Yeong Chan (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2017)
Form-critical studies in the ethical basis of Isaiah has reached an impasse. Many ethical injunctions in Isaiah 1-39 does not fit into either wisdom or legal categories according to form-critical approaches. This article will re-examine the ethical basis of Isaiah 1-39 by employing a literary-canonical approach.